From a Lexical Verb to a Pragmatic Marker: The Case of the French falloir ‘have to/must’ - Valiukienė, Vita (Verbum, 2022)
The paper seeks to present a semantico-functional analysis of the French verb falloir. The empirical data are obtained from a parallel corpus – the Corpus Parallèle de Textes Littéraires (CTLFR-LT), which is composed of French literary texts and their translations into Lithuanian. The paper uses quantitative, qualitative and comparative methods. It is based on the studies focusing on the polysemy of modal verbs (Chu 2010; Dendale 1994; Kronning 1988; Le Querler 2001; Rossari 2012) as well as on the development of discourse markers in language (Dostie 2004; Vold 2008). The findings show that the verb falloir, while maintaining its core meaning of necessity, can express conjecture. When it is used in patterns together with verbs of saying (verba cogitandi and dicendi) and verbs of visual perception, falloir no longer functions as a marker of necessity and becomes a pragmatic marker of connection and argumentation. The analysis of the translations of the French verb falloir into a typologically different language, Lithuanian, has also confirmed the entrenched use of the verb in question in the modal field of necessity and its rich functional potential in the French literary texts. The paper contributes to the existing contrastive studies between the French and Lithuanian languages, which are not numerous. The findings of the research could serve didactic purposes as well as add to the field of translation studies.